AN EXPERIMENTAL UNDERSTANDING OF TRANSACTION UTILITY IN PIRACY - Basu, Paulomi; Banerjee, Tanmoyee; Mitra, Santanu (Journal of economic development, 2022)
The present paper conducts a laboratory experiment with a sample of 209 students from Jadavpur University, Kolkata, India, within age group of 18-23 to study the prevalence of transaction utility in product piracy decision of the consumers. The experiment with four different treatments, treating price of original good as reference price for potential pirates uses standard descriptive statistics and logistic regression with clustered standard error at individual level to show that transaction utility is the statistically significant factor affecting the likelihood of piracy. Further, males and students belonging to Humanities are more inclined to product piracy.